Role of the Gut Microbiota-Intestinal Barrier Axis in Enterogenic Infection Complicating Acute Pancreatitis and Early Intervention with Probiotics: An Exploratory Clinical Study - Dong, Han; Feng, Chen (Journal of Contemporary Medical Practice, 2026)
Objective: To investigate the dynamic changes in the gut microbiota-intestinal barrier axis in patients with moderately severe or severe acute pancreatitis (MSAP/SAP) and to evaluate the clinical efficacy and safety of early multi-strain probiotic intervention in preventing peripancreatic infection. Methods: This prospective, randomized, double-blind, placebo-controlled study enrolled 120 patients with MSAP/SAP (onset to admission ≤48 h), randomly assigned to a probiotic group (n=60) and a placebo group (n=60). The probiotic group received a multi-strain preparation (Lactobacillus, Bifidobacterium, Saccharomyces boulardii; ≥1×10¹⁰ CFU/dose) twice daily for 14 days, while the control group received an identical placebo. The primary endpoint was the incidence of peripancreatic necrotic tissue infection within 28 days. Secondary endpoints included gut microbiota diversity (16S rRNA sequencing), serum intestinal barrier markers (I-FABP, D-lactate, Zonulin), inflammatory markers (CRP, PCT, IL-6), duration of antibiotic use, ICU stay, total hospital stay, 28-day mortality, and adverse events. Results: A total of 115 patients (probiotic group 58, placebo group 57) were included in the final analysis. Baseline characteristics were comparable between groups. The incidence of peripancreatic infection was significantly lower in the probiotic group compared to the placebo group (17.2% vs. 31.6%; RR=0.55, 95%CI 0.31-0.97, P=0.040; NNT=7.0). Probiotic intervention was an independent protective factor after adjusting for confounders (OR=0.48, 95%CI 0.24-0.95, P=0.035). The probiotic group also showed significantly shorter duration of antibiotic use [12 (8, 16) vs. 16 (11, 22) days, P=0.013] and ICU stay [9 (5, 14) vs. 13 (8, 19) days, P=0.021]. Microbiota analysis revealed that from day 3 onwards, infected patients exhibited significant enrichment of Enterococcus and Fusobacterium, and depletion of Bifidobacterium and Faecalibacterium (LDA>2, q<0.05). I-FABP levels were significantly higher in the infection group (P<0.001). A predictive model based on three genera at day 3 achieved an AUC of 0.824 (95%CI 0.746-0.902) for predicting subsequent infection. No significant differences were observed in 28-day mortality or adverse events between groups. Conclusion: Dynamic imbalance of the gut microbiota-intestinal barrier axis plays a crucial role in the pathogenesis of peripancreatic infection in MSAP/SAP patients. Early multi-strain probiotic intervention within 48 hours of onset can significantly reduce the incidence of peripancreatic infection, shorten antibiotic use and ICU stay, and is safe. Specific microbial markers demonstrate potential value for early warning of infection.